Association of Oxidative-Stress-Related Gene Polymorphisms with Pain-Related Temporomandibular Disorders and Oral Behavioural Habits - Ema Vrbanović; Marko Zlendić; Koraljka Gall Trošelj; Marko Tomljanović; Kristina Vuković Đerfi; Iva Z. Alajbeg (MDPI AG, 2023)
The frequency of selected polymorphisms, one in each gene coding for proteins with antioxidative properties (CAT(rs1001179), SOD2(rs4880), GPX1(rs1050450), and NQO1(rs689452)), was compared between patients suffering from pain-related temporomandibular disorders (TMDp; n = 85) and control subjects (CTR; n = 85). The same was evaluated when participants were divided with respect to oral behavioural habits frequency into high-frequency parafunction (HFP; n = 98) and low-frequency parafunction (LFP; n = 72) groups. Another aim was to investigate whether polymorphisms in these genes can be associated with participants' psychological and psychosomatic characteristics. Polymorphisms were genotyped using the genomic DNA extracted from buccal mucosa swabs and real-time TaqMan genotyping assays. No differences in genotype distribution between TMDp patients and control subjects were found. Still, TMDp patients who were homozygous for minor allele A, related to the GPX1 polymorphism rs1050450, reported significantly more waking-state oral behaviours than GA + GG genotype carriers (score: 30 vs. 23, p = 0.019). The frequency of genotype AA for rs1050450 polymorphism was higher in HFP than in LFP participants (14.3% vs. 4.2%, p  = 0.030). The most important predictors of waking-state oral behaviours were depression, anxiety, AA genotype (rs1050450), and female sex. The explored gene polymorphisms were not found to be significant risk factors for either TMDp or sleep-related oral behaviours. The association of waking-state oral behaviours with selected gene polymorphisms additionally supports previous assumptions that daytime bruxism is more closely linked to various stress manifestations, which might also be reflected through the variability related to the cellular antioxidative activity.